Safety training transfer in chemical manufacturing: The role of personality traits and learning motivation - Anasuya K Lingappa (Taylor & Francis Group, 2020)
This study investigates the influence of personality characteristics and employees’ motivation to learn on safety training transfer, in the context of a chemical manufacturing company. The study focuses on five personality characteristics: Locus of Control, Extraversion, Conscientiousness, Neuroticism, and Risk-Taking Propensity. Also, the roles of Motivation to Learn (MTL) and Motivation to Transfer (MTT) on Safety Training Transfer (STT) are examined. The data for the study was collected using a self-report questionnaire survey from 226 employees from an Indian subsidiary of one of the largest chemical companies in the world. The obtained responses were analyzed using Structural Equations Modelling (SEM), Partial Least Squares (PLS) method. The results of the analysis show that among the five personality factors considered, Conscientiousness and Locus of control positively influenced STT through MTL whereas Risk Taking Propensity had a negative relationship. Extraversion and Neuroticism did not indicate any significant influence. This paper adds to academic knowledge of safety training by analyzing how employees’ personality factors influence MTL, MTT, and STT behavior. The results shed light on safety training in the context of the chemical industry operational in a developing nation, a combination rarely found in previous studies.